Revised Second Five Year Plan - Uttar Pradesh - Planning Commission (Planning Commission)
This is the basic ceiling fixed by the Commission in their letter quoted above. The State Government -have made certain minor adjustments within this ceiling, as the consolidated statement of expenditure will show, the two important ones being the new schemes of Tourist Traffic and Sports for which sums of Rs 25 and 35 lakhs have respectively been provided in the Revised Plan.
Planning Commission